Chitosan loaded RNA polymerase inhibitor nanoparticles increased attenuation in toxin release from Streptococcus pneumonia - Fulwah Yahya Alqahtani; Fadilah Sfouq Aleanizy; Hamad M. Alkahtani; Eram El Tahir; Siddique Akber Ansari; Atheer Alharbi; Asmaa Al-Bdrawy; Faiyaz Shakeel; Nazrul Haq; Lamees S. Al-Rasheed; Rihaf Alfaraj; Abdullah K. Alshememry; et al. (Elsevier, 2023)
Background: Multidrug-resistant (MDR) bacterial infections have become an emerging health concern around the world. Antibiotics resistance among S. pneumoniae strains increased recently contributing to increase in incidence of pneumococcal infection. This necessitates the discovery of novel antipnemococcal such as compound C3-005 which target the interaction between RNA polymerase and σ factors. Chitosan nanoparticles (CNPs) exhibited antibacterial activity including S. pneumonia. Therefore, the aims of the current investigation were to formulate CNPs loaded with C3-005 and characteristic their antimicrobial properties against S. pneumonia. Methods: The CNPs and C3-005 loaded CNPs were produced utilizing ionic gelation method, and their physicochemical characteristics including particle size, zeta potential, polydispersity index (PDI), encapsulation efficiency (EE%), and in vitro release profile were studied. Both differential scanning calorimetry (DSC) and fourier transform infrared spectroscopy (FTIR) were used for chemical characterization. The synthesized NPs' minimum inhibitory concentration (MIC) was determined using killing assay and broth dilution method, and their impact on bacteria induced hemolysis were also studied. Results: The NPs encapsulating C3-005 were successfully prepared with particle size of 343.5 nm ± 1.3, zeta potential of 29.8 ± 0.37, and PDI of 0.20 ± 0.03. 70 % of C3-005 were encapsulated in CNPs and sustained release pattern of C3-005 from CNPs was revealed by an in vitro release study. CNPs containing C3-005 exhibited higher antipnomcoccal activity with MIC50 of 30 µg/ml when compared with C3-005 and empty CNPs alone. The prepared C3-CNPs showed a reduction of bacterial hemolysis in a concentration-related (dependent) manner and was higher than C3-005 alone. Conclusions: The findings of this study showed the potential for using C3-005 loaded CNPs to treat pneumococcal infection.